Computer-based assessment of unilateral spatial neglect: A systematic review - Giannakou, Ioanna; Lin, Dan; Punt, David (Frontiers in Neuroscience, 2022)
Background To date, no gold standard exists for the assessment of unilateral spatial neglect (USN), a common post-stroke cognitive impairment, with limited sensitivity provided by currently used clinical assessments. Extensive research has shown that computer-based (CB) assessment can be more sensitive, but these have not been adopted by stroke services yet. Objective We conducted a systematic review providing an overview of existing CB tests for USN to identify knowledge gaps and positive/negative aspects of different methods. This review also investigated the benefits and barriers of introducing CB assessment tasks to clinical settings and explored practical implications for optimizing future designs. Methodology We included studies that investigated the efficacy of CB neglect assessment tasks compared to conventional methods in detecting USN for adults with brain damage. Study identification was conducted through electronic database searches (e.g., Scopus), using keywords and standardized terms combinations, without date limitation (last search: 08/06/2022). Literature review and study selection were based on prespecified inclusion criteria. The quality of studies was assessed with the quality assessment of diagnostic accuracy studies tool (Quadas-2). Data synthesis included a narrative synthesis, a table summarizing the evidence, and vote counting analysis based on a direction of effect plot. Results A total of 28 studies met the eligibility criteria and were included in the review. According to our results, 13/28 studies explored CB versions of conventional tasks, 11/28 involved visual search tasks, and 5/28 other types of tasks. The vote counting analysis revealed that 17/28 studies found CB tasks had either equal or higher sensitivity than conventional methods and positive correlation with conventional methods (15/28 studies). Finally, 20/28 studies showed CB tasks effectively detected patients with USN within different patient groups and control groups (17/28). Conclusions The findings of this review provide practical implications for the implementation of CB assessment in the future, offering important information to enhance a variety of methodological issues. The study adds to our understanding of using CB tasks for USN assessment, exploring their efficacy and benefits compared to conventional methods, and considers their adoption in clinical environments.